Nitrogen enriched mesoporous organic polymer anchored copper(ii) material: an efficient and reusable catalyst for the synthesis of esters and amides from aromatic systems1. Issue 14 (14th April 2015) - Molla, Rostam Ali; Iqubal, Md. Asif; Ghosh, Kajari; Kamaluddin; Islam, Sk. Manirul
<x xml:space="preserve">Abstract</x> New mesoporous polymer anchored copper acetate (Cu-mPMF) has been synthesized and well characterized. The catalytic performance of this complex has been tested for the synthesis of esters and amides.